Contrast-Enhanced Computed Tomography Evaluation of Hepatic Metastases in Breast Cancer Patients before and after Cytotoxic Chemotherapy or Targeted Therapy. Issue 4 (November 2015) - He, Hongying; Cai, Chunyan; Charnsangavej, Chusilp; Theriault, Richard L.; Green, Marjorie; Quraishi, Mohammad A.; Yang, Wei T.
Purpose: To evaluate change in size vs computed tomography (CT) density of hepatic metastases in breast cancer patients before and after cytotoxic chemotherapy or targeted therapy. Methods: A database search in a single institution identified 48 breast cancer patients who had hepatic metastases treated with either cytotoxic chemotherapy alone or targeted therapy alone, and who had contrast-enhanced CT (CECT) scans of the abdomen at baseline and within 4 months of initiation of therapy in the past 10 years. Two radiologists retrospectively evaluated CT scans and identified up to 2 index lesions in each patient. The size (centimeters) of each lesion was measured according to Response Evaluation Criteria in Solid Tumors (RECIST) criteria, and CT density (Hounsfield units) was measured by drawing a region of interest around the margin of the entire lesion. The percent change in sum of lesion size and mean CT density on pre- and post-treatment scans was computed for each patient; results were compared within each treatment group. Results: Thirty-nine patients with 68 lesions received cytotoxic chemotherapy only; 9 patients with 15 lesions received targeted therapy only. The mean percent changes in sum of lesion size and mean CT density were statistically significant within the cytotoxic chemotherapy group before and after treatment, but not significant in the targeted therapy group. The patients in the targeted therapy group tend to have better 2-year survival. The patients who survived at 2 years tend to have more decrease in tumour size in the cytotoxic chemotherapy group. Conclusion: Cytotoxic chemotherapy produced significant mean percent decrease in tumour size and mean CT density of hepatic metastases from breast cancer before and after treatment, whereas targeted therapy did not. Nonetheless, there is a trend that the patients in the targeted therapy group had better 2-year survival rate. This suggests that RECIST is potentially inadequate in evaluating tumour response in breast cancer liver metastases treated with targeted therapy alone, calling for an alternative marker for response evaluation in this subset of patients.